BEHAVIOUR OF INLINE KNOCKOUT MACHINE OPERATING UNDER VIBRATION - Vishal Shrimandhar Masutage; Mukund V. Kavade (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Inline knockout machine is designed to separate sand and castings from mold box. Vibration is controlled by unbalanced weights provided on each side of spindle. Failure of the components such as vibrating box, vibrating frame, and damper takes place after certain number of cycles. Modal analysis and harmonic analysis have been carried out based on dynamic analysis technology.